2012
DOI: 10.3402/tellusa.v64i0.15829
|View full text |Cite
|
Sign up to set email alerts
|

On the contribution of lakes in predicting near-surface temperature in a global weather forecasting model

Abstract: A B S T R A C TThe impact of lakes in numerical weather prediction is investigated in a set of global simulations performed with the ECMWF Integrated Forecasting System (IFS). A Fresh shallow-water Lake model (FLake) is introduced allowing the coupling of both resolved and subgrid lakes (those that occupy less than 50% of a grid-box) to the IFS atmospheric model. Global fields for the lake ancillary conditions (namely lake cover and lake depth), as well as initial conditions for the lake physical state, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
139
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 10 publications
1
139
0
Order By: Relevance
“…As RCMs and standalone lake models are being applied to increasingly remote lakes, the need to consider this data quality issue grows (Martynov et al, 2010). Finally, in the absence of initialisation data, several approaches to lake temperature initialisation and spin-up have been applied in the past (Kourzeneva et al, 2008;Mironov et al, 2010;Balsamo et al, 2012;Hernández-Díaz et al, 2012;Rontu et al, 2012). Hence, a systematic study of the sensitivity of the model to different sources of error is appropriate.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…As RCMs and standalone lake models are being applied to increasingly remote lakes, the need to consider this data quality issue grows (Martynov et al, 2010). Finally, in the absence of initialisation data, several approaches to lake temperature initialisation and spin-up have been applied in the past (Kourzeneva et al, 2008;Mironov et al, 2010;Balsamo et al, 2012;Hernández-Díaz et al, 2012;Rontu et al, 2012). Hence, a systematic study of the sensitivity of the model to different sources of error is appropriate.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…In these environments small water bodies can represent up to 10 % of the local land surface area (MacKay et al, 2009;Nordbo et al, 2011;Bouin et al, 2012). Although few studies have focused specifically on analysing the impact of small lakes on regional climates, authors such as MacKay et al (2009), Balsamo et al (2012) and Martynov et al (2012) have indicated the potential importance of these water bodies in modifying the local climates of regions where they are abundant. Currently, the effect of small to medium size lakes in most numerical weather prediction (NWP) and climate modelling systems is either entirely ignored or crudely parameterized (Mironov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, at the regional and local scales, the lake surface can be very large, as is the case in Northern Europe, Asia and North America. The high density of lakes in these regions may affect the regional climate (Balsamo et al, 2012;Kheyrollah Pour et al, 2012). In particular, on summer days, the presence of a lake tends to stabilise the atmosphere, in contrast with land, where turbulence tends to develop.…”
Section: Introductionmentioning
confidence: 99%